Comparison of PCR and Plaque Assay for Detection and Enumeration of Coliphage in Polluted Marine Waters - Rose, J. B. (1997)
A total of 68 marine samples from various sites impacted by sewage and storm waters were analyzed by both the plaque assay and a reverse transcriptase (RT) PCR technique for F(sup+)-specific coliphage. The coliphage levels detected by the plaque assay averaged 1.90 x 10(sup4) PFU/100.0 ml. Using a most probable number (MPN) PCR approach, the levels averaged 2.40 x 10(sup6) MPN-PCR units/100.0 ml. Two samples were positive by RT-PCR but negative by plaque assay, and 12 samples were positive by plaque assay but negative by RT-PCR (levels lower than 11.00 PFU/100.0 ml). The host system used for the plaque assay may detect somatic coliphage in addition to the F(sup+)-specific coliphage. When it is used as an indicator of pollution, contamination may be missed with more restrictive systems. The difference in results may be due to the sensitivity, specificity, or inhibition of RT-PCR in marine samples. This study provides information on quantifying PCR results by an MPN method and insights into interpretation of PCR data for detection of viruses in marine environments.